English Literacy Activities at Jembatan Budaya Primary School Bali - Puspitasari, Putu Indah (International Journal of Elementary Education, 2021)
This case study aimed at investigating the kinds of English literacy activities implemented at Jembatan Budaya Primary School. There were three teachers who teach on the 1st, 2nd, and 3rd grade assigned as the subjects of this study. The data were collected by employing questionnaire, interview guide, and observation checklist as the instruments. The procedures in collecting the data were started from distributing questionnaire to the subjects, conducting interview by using an interview guide, and conducting classroom observation. The data were analyzed by Creswell (2012) descriptive analysis consists of data organization, coding, describing and developing themes, reporting the findings, interpreting, and validation. The result of the study showed that there were eight types of literacy activities conducted in Jembatan Budaya Primary School found in this study, namely Directed Reading - Thinking Activity, guided reading, multimedia-assisted reading, thinking aloud, reading aloud, dictation, alphabet recognition, and writing. It implies that various literacy activities with appropriate methods were conducted to develop students’ literacy.